ショウワキチ タイキ チュウ ノ ニサンカタンソ - 村山, 治太; ムラヤマ, ハルタ; MURAYAMA, Haruta (国立極地研究所, 1977)
P(論文) 第13次越冬観測の際,南極昭和基地における地表大気中の二酸化炭素濃度を,非分散型赤外線ガス分析計を使用して,1972年3月から1973年1月まで測定した.測定器の更正には日本から運んだボンベづめ更正ガスを用いた.昭和基地は69°S, 39.5°Eに位置し,測定器を設置した研究室の標高は13mである.測定結果は317 ppm～328 ppmと分散しており,次のような季節変化の傾向がみられた.1)南極の夏季は高い値を示した(324±4 ppm). 2)南極の夏が終わると急速に低下した.3)南極の冬の前半期(5,6,7月)は低い値を示した(319±4 ppm).4)南極の冬の後半期(8～11月)にはわずかながら増加の傾向を示した(319±4ppm→323±3 ppm).5)11ヵ月の平均値は322±7 ppmであった.PALES and KEELING (J. Geophys. Res., 70, 6053, 1965)およびBROWN and KEELING (J. Geophys. Res., 70, 6077, 1965)によるハワイおよび南極点での観測結果とはやや異なったが,その原因についてはさらにくわしい研究が必要である. During the 13th Japanese Antarctic Research Expedition in 1972-1973 the determination of the carbon dioxide content of the surface air was carried out at Syowa Station (69°S, 39.5°E) in Antarctica, by using Infra-Red Gas Analyzer. The station is located on East Ongul Island, 5km off the Antarctic Continent, and the elevation of the laboratory is about 13 m above sea level. The mean value of the carbon dioxide content of the dry surface air was 322±7 ppm during the period from March 1972 to January 1973. Some of the seasonal variations observed were as follows: 1) The carbon dioxide content showed high values in the Antarctic summer season (324±4 ppm). 2) At the end of the Antarctic summer, the content decreased abruptly. 3) Low values were observed in early winter-May, June and July (319±4 ppm). 4) Gradual increase was observed late winter-August, September, October and November (319±4 ppm → 323±3 ppm). 5) The mean value for 11 months was 322±7 ppm. The annual variation pattern of the carbon dioxide content at Syowa Station showed a slight difference from the results obtained by PALES and KEELING (J. Geophys. Res., 70, 6053, 1965) at Hawaii and by BROWN and KEELING (J. Geophys. Res., 70, 6077, 1965) at the South Pole. departmental bulletin paper